2018
DOI: 10.2118/189218-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Field Measurements and Data-Handling Procedures on Carbonate- and Sulfide-Scale Prediction

Abstract: Summary Carbonate and sulfide scales are directly coupled together and differ from other inorganic scales because they are intimately linked to the in-situ concentrations of carbon dioxide (CO2) and hydrogen sulfide (H2S), which influence the local pH and availability of reactive species. The CO2 in aqueous solutions has the most significant effect on the system pH, on the solution content of bicarbonate ion (HCO3–), and on the final alkalinity. However, the presence of H2S in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The authors also looked at field measurement errors and concluded that the three key field measurements for reliable carbonate scale predictions are CO 2(g) , H 2 S (g) , and Ca 2+ …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also looked at field measurement errors and concluded that the three key field measurements for reliable carbonate scale predictions are CO 2(g) , H 2 S (g) , and Ca 2+ …”
Section: Discussionmentioning
confidence: 99%
“…6,9 The authors also looked at field measurement errors and concluded that the three key field measurements for reliable carbonate scale predictions are CO 2(g) , H 2 S (g) , and Ca 2+ . 10 In this paper, the authors addressed the problem of choosing between different software, EOS, and input (or default) parameters for the PVT calculations.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…needed (Kan and Tomson 2012). The produced water pH is usually determined by a balance between the gas phase acid gases, H 2 S and CO 2 , and the water phase active anions, HCO 3 -, CO 3 2-, carboxylates (such as acetate), HS -, S 2and OHand each of these anions is difficult to measure accurately (for a discussion of these analytical issues, see corresponding references (Kan and Tomson 2012;Kan et al 2019;Ness and Sorbie 2019). Also, for many wells the temperature, pressure, and flow rates are not known accurately enough to support squeeze/resqueeze decisions.…”
Section: Proper Sampling and Accurate Analysismentioning
confidence: 99%